Tolerance value transmission of multi-ethnic and multi-religious society : a systematic literature review approach - Rachmawati, Depy Eka; Kusumawati, Dwi Arsinta; Khasanah, Tri; Purwandari, Eny (Penerbit Universiti Kebangsaan Malaysia, 2021)
Indonesia is a country that has ethnic and religious pluralism which is the wealth of the Indonesian nation as well as a threat to potential conflicts caused by intolerant behavior towards existing pluralism. This article aims to provide a comprehensive overview of the tolerance value transmission of multi-ethnic and multi-religious society through a systematic literature review approach. The research method employed PRISMA flow (Preferred Reporting Item for Systematic Review and Meta-Analytic) with the keywords, namely tolerance, value transmission, religion, and ethnicity. The search for articles used publish or perish and several journal portals, such as Proquest and Sciencedirect. The screening process was carried out systematically using four screening stages, namely elimination of duplicate articles, elimination of non-full-text scientific journals, eligibility test for articles using the keywords used, and thematic and content screening. Through this process, ten journals relevant to the topic were found for further analysis. This research concluded that tolerance behavior is significant in a pluralistic society in any country. Various efforts to transmit the value of tolerance, through education, such as religious education, multi-cultural education curriculum approach, family education, and a cultural approach with ancestral wisdom.